2019
DOI: 10.3329/bjz.v47i2.44334
|View full text |Cite
|
Sign up to set email alerts
|

Predator performance of Coccinella transversalis and its molecular identification

Abstract: Predatory efficacy of Coccinella transversalis (Coleoptera: Coccinellidae) on three detrimental agriculturally important aphids (Aphis craccivora, A. fabae and A. gossypii) was studied under laboratory condition. The 4 th instar larvae of C. transversalis consumed highest (21.56 ± 1.72) number of A. craccivora aphids followed by A. fabae (12.33 ± 1.74) and A. gossypii (13.99 ± 0.77). Life cycle studies of C. transversalis on the above three aphid species revealed that it took maximum (27.66 ± 3.06) days to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The period of first instar grub was in range of 2 to 4 with an average of 2.60± 0.638 days in the present studies. Sarker et al (2019) reported the first instar grub period of C. transversalis were 2.66± 1.15 and 2.66± 0.58 days on A. craccivora and A. gossypii, respectively. Mari et al (2016) reported the period of first instar grub of C. undecimpunctata on mustard aphid, L. erysimi which was 5.23 days.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The period of first instar grub was in range of 2 to 4 with an average of 2.60± 0.638 days in the present studies. Sarker et al (2019) reported the first instar grub period of C. transversalis were 2.66± 1.15 and 2.66± 0.58 days on A. craccivora and A. gossypii, respectively. Mari et al (2016) reported the period of first instar grub of C. undecimpunctata on mustard aphid, L. erysimi which was 5.23 days.…”
Section: Resultsmentioning
confidence: 94%
“…Second instar grub period were found to be 2 to 4 with an average of 2.76± 0.655 days. Sarker et al (2019) reported the second instar grub period of C. transversalis 2.66± 0.58 days on A. fabae. The third instar grub period of C. transversalis on mustard aphid, Lipaphis erysimi varied from 2-5 days, with an average of 3.66± 0.831 days in present studies which is in agreement with Sarker et al (2019) who reported the third instar grub period of 3.66± 0.58 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, E. admirabilis is a pest. C. transversalis is a predator of Aphis gossypii (Glover) (Efendi et al 2018;Sarker et al 2019), A. craccivora, and A. fabae (Sarker et al 2019). No reports have stated that C. transversalis was a vector of a particular pathogen.…”
Section: Diversity Of Pests and Predators In Chili Plantsmentioning
confidence: 99%